AB0214 A Stabilized Neuropeptide Immunotherapy Abrogates Bleomycin-Induced Pulmonary Fibrosis. (10th June 2014) - Woloszynek, J.; Etzel, K.; Vernes, J.; McIntosh, D.; Moore, C.; Haq, M.; Lopez, H.; Haq, S.
Abstract : Background: Stabilised caprine corticotrophin releasing hormone is long acting neuropeptide that targets its cognate receptor in the skin and hypothalamus. Objectives: The aim of this study was to examine the role of stabilized-release caprine corticotrophin releasing hormone-1 (SR-CCRH-1) an extract from hyperimmune caprine sera (HICS) could act as an anti-fibrotic agent in the murine bleomycin (BLM)-induced pulmonary fibrosis model. Methods: Two parallel studies were used; one functional and the other pathology-based, using age-matched C57BL/6 male and female mice, n=8-12 per treatment group (saline control, naïve serum control, bleomycin/saline, bleomycin/naïve and bleomycin/SR-CCRH-1), were injected daily with (100 μg s.c.) of SR-CCRH-1 or naïve serum in the respective group using a double-blind experimental protocol from day 7 post-BLM gavage until day 28. Study mice were administered with 0.09 units of BLM in 50 μl volume by gavage at the start of the study on day 1. Results: The results showed on immunohistochemical staining of lung biopsies [multiple sections taken per group (n=6)] using H&E, Masson's Trichrome indicated that SR-CCRH-1 significantly inhibited pulmonary fibrosis (p=0.019) and significantly reduced the inflammatory cellular infiltrate and alveolar macrophage infiltrate in the BLM/SR-CCRH-1 group relative to all control groups. ELISA studies from pulmonary homogenates further confirmed and showed that SR-CCRH-1 significantly reduced PIIINP levels (p=0.0437) in the lung of animals treated with BLM. ELISA studies on serum taken from the study groups further confirmed significant inhibition of IL-12p70 (p=0.046), MMP-9 (p=0.047), but not of MMP-13 (p=0.658). Bronchoalveolar lavage showed significant inhibition of the monocyte chemo-attractant protein-1 (MCP-1) in the SR-CCRH-1 versus BLM/vehicle controls (p=0.039). A separate body plethsmography study using the BUXCO system was used to determine the pulmonary lung function of animals at day 10 and 28 days during the study. Animals were exposed to either air or a 5% CO2 stress-challenge. Significant maintenance of lung function in the BLM/SR-CCRH-1 group compared to the BLM/naïve serum group but importantly, comparable to the naïve serum control group was noted, as measured by changes in the minute volume (p=0.003), tidal volume (p=0.008) but not frequency when animals were exposed to a 5% CO2 challenge at 28 days. The results indicate that SR-CCRH-1 blocked significantly the functional and pathological deterioration associated with BLM-induced pulmonary fibrosis. The study taken together provide a novel targeted approach that focused on the CRH-1 receptor in the lung parenchyma and hypothalamo-pituitary-adrenal axis that lead to augmentation of pulmonary fibrosis. Conclusions: To that end, in a recently completed phase II double blind placebo controlled trial in established late-stage diffuse systemic sclerosis using SR-CCRH-1 pointed to an efficacy signal with improved pulmonary FVC in the active treatment arm, and a favourable safety/tolerability profile. Disclosure of Interest: J. Woloszynek: None declared, K. Etzel: None declared, J. Vernes Employee of: employee, D. McIntosh Shareholder of: Shareholder, Consultant for: Consultant, C. Moore Shareholder of: Shareholder, M. Haq Shareholder of: Shareholder, H. Lopez: None declared, S. Haq: None declared DOI: 10.1136/annrheumdis-2014-eular.5969